Comorbidities associated with poor outcomes following operative hammertoe correction in a geriatric population - Samuel Maidman BA; Jason Bariteau MD; Stephanie Boden BA; Allison Boden BA; Shay Tenenbaum MD (Foot & Ankle Orthopaedics, 2018)
Category: Lesser Toes Introduction/Purpose: Hammertoe deformities are one of the most common lesser foot deformities and are extremely prevalent in the geriatric population. When nonoperative treatment fails, surgical correction can improve functional status and pain. While complications following these surgeries are rare, older patients with comorbid conditions are often considered worse operative candidates due to an increased risk of adverse outcomes. The aim of this study is to determine if specific comorbidities or perioperative variables are associated with increased complications or unsuccessful outcomes following operative hammertoe correction in geriatric patients. Methods: Prospectively collected data was reviewed on 31 consecutive patients aged 60 or older who underwent operative correction of hammertoe deformity. Patient demographics, comorbidities, perioperative variables, and postoperative complications were recorded from their electronic medical records. Clinical outcomes were assessed utilizing preoperative and postoperative Visual Analogue Scale (VAS) and Short Form Health Survey Physical Component Score (SF-36 PCS) with a minimum of six-month follow-up. Data was examined using Fisher’s method and multivariable analysis. Results: 29.0% (9/31) of patients had a history of smoking, 61.2% (19/31) were on anticoagulant therapy, 19.4% (6/31) had osteoporosis, 16.1% (5/31) had rheumatoid arthritis, and 9.7% (3/31) had diabetes mellitus. The mean tourniquet and operative times were 65.7 (SE=6.2) and 95.4 (SE=7.4) minutes, respectively. Postoperative complications occurred in 12.9% (4/31) of patients with the most prevalent being wound infections that were treated with antibiotics in 9.7% (3/31). Impaired wound healing, joint nonunion, and the need for revision surgery each occurred in 3.2% (1/31) of patients. Mean 6-month improvement in VAS was 2.1 (SE=0.5) and mean improvement in SF-36 PCS was 10.2 (SE = 3.4). No significant association was found between comorbidities or perioperative variables and postoperative complications or improved outcomes. Conclusion: No specific comorbidities or perioperative variables were identified that increase the risk for unsuccessful surgical correction of hammertoe deformities. While comorbidities in the geriatric population have traditionally been thought to increase complication rates and lead to poor outcomes, further research in this area is warranted. Comorbidities should not necessarily be a deterrent for geriatric patients pursuing operative hammertoe correction.